Stilleben. - Rychlik, Otmar; Galerie Freiberger, Mürzzuschlag (Mürzzuschlag : Walter Buchebner Gesellschaft, 1989)
Bepperling, Tina ; Egerer, Evelyne ; Kandl, Johanna ; Kowanz, Brigitte ; Maderthaner, Franziska ; Pellikan, Christine ; Schlegel, Eva ; Stoisser, Suse ; Strobl, Ingeborg ; Winkler, Bernhard
Stilleben, Galerie Freiberger, Mürzzuschlag, 1989
boek